Comparison of Major Sudden Stratospheric Warming Impacts on the Mid-Latitude Mesosphere Based on Local Microwave Radiometer CO Observations in 2018 and 2019 - Yu Shi; Valerii Shulga; Oksana Ivaniha; Yuke Wang; Oleksandr Evtushevsky; Gennadi Milinevsky; Andrew Klekociuk; Aleksey Patoka; Wei Han; Dmitry Shulga (Remote Sensing, 2020)
In this paper, a comparison of the impact of major sudden stratospheric warmings (SSWs) in the Arctic in February 2018 (SSW1) and January 2019 (SSW2) on the mid-latitude mesosphere is given. The mesospheric carbon monoxide (CO) and zonal wind in these two major SSW events were observed at altitudes of 70–85 km using a microwave radiometer (MWR) at Kharkiv, Ukraine (50.0°N, 36.3°E). Data from ERA-Interim and MERRA-2 reanalyses and Aura Microwave Limb Sounder measurements were also used. It is shown that: (i) The differences between SSW1 and SSW2, in terms of local variability in zonal wind, temperature, and CO in the stratosphere and mesosphere, were clearly defined by the polar vortex (westerly in cyclonic circulation) and mid-latitude anticyclone (easterly) migrating over the MWR station, therefore; (ii) mesospheric intrusions of CO-rich air into the stratosphere over the Kharkiv region occurred only occasionally, (iii) the larger zonal wave 1–3 amplitudes before SSW1 were followed by weaker polar vortex recovery than that after SSW2, (iv) the strong vortex recovery after SSW2 was supported by earlier event timing (midwinter) favoring vortex cooling due to low solar irradiance and enhanced zonal circulation, and (v) vortex strengthening after SSW2 was accompanied by wave 1–3 amplification in March 2019, which was absent after SSW1. Finally, the influence of the large-scale circulation structures formed in individual major SSW events on the locally recorded characteristics of the atmosphere is discussed.